2006
DOI: 10.2495/su060441
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of plain-woven CFRP reinforced by spread fiber tow during and after drop-weight impact

Abstract: For this paper, the impact behaviors and the damage state of plain-woven CFRP reinforced by spread tow due to falling weight were evaluated. Stress-Strain responses of the CFRP using spread tows were investigated under drop-weight impact loading at room temperature. Three leveled impact energy was applied to the surface of the specimen in the drop-weight test. The peak load and absorbed energy were then compared with those of a conventional one and the experimental results showed that the peak load and absorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…A hemispherical impactor specified in ASTM D7136 ensures the maximum contact area and internal damage area at a relatively small depth, whilst impacts with sharp prismatic impactors cause deeper damages to the material structure and have relatively small contact areas. The paper Toyota et al (2006) examined different materials and studied static strength after impact (SAI) and fatigue life after impact (FAI), which concluded that reinforcing with spread tow is effective for improving the mechanical properties of plain-woven carbon-fibre reinforced plastic (CFRP) during and after impact loading. The experimental data of residual strength obtained by the methods described above can be used for a design utilising reliability methods (Mohabeddine et al, 2021a, b), residual strength models for cyclic and static loads (Mohabeddine et al, 2021a, b), as well as parameters in analytical models of fracture mechanics (Mohabeddine et al, 2022).…”
Section: Ijsi 141 44mentioning
confidence: 99%
“…A hemispherical impactor specified in ASTM D7136 ensures the maximum contact area and internal damage area at a relatively small depth, whilst impacts with sharp prismatic impactors cause deeper damages to the material structure and have relatively small contact areas. The paper Toyota et al (2006) examined different materials and studied static strength after impact (SAI) and fatigue life after impact (FAI), which concluded that reinforcing with spread tow is effective for improving the mechanical properties of plain-woven carbon-fibre reinforced plastic (CFRP) during and after impact loading. The experimental data of residual strength obtained by the methods described above can be used for a design utilising reliability methods (Mohabeddine et al, 2021a, b), residual strength models for cyclic and static loads (Mohabeddine et al, 2021a, b), as well as parameters in analytical models of fracture mechanics (Mohabeddine et al, 2022).…”
Section: Ijsi 141 44mentioning
confidence: 99%
“…With a higher molding pressure, the flexural properties become slightly better, but these were within the margin of error (Figure 12). There have been few reports about the mechanical properties of composites made from commingled carbon/nylon fiber fabrics, Toyota et al evaluated the mechanical properties of fabrics made from spread commingled carbon fiber yarns coated with nylon resin, and reported that the fabrics made from this had a 20% higher elastic modulus and strength than those made from unspread yarns [27]. The tensile modulus of carbon fiber TR50S12L is 235 GPa, therefore, if the volume fraction is 39 % and the nylon fibers' modulus are ignored, the tensile modulus of composites will be 91.7 GPa if the carbon fibers are aligned in the tensile direction.…”
Section: Four-point Flexural Testmentioning
confidence: 99%
“…On the other hand, to fully demonstrate the strength of carbon fiber, one study shortened the impregnation distance in the film stacking method by applying “open continuously reinforcing fiber tow,” a technique to thinly and widely spread carbon fiber bundles [ 26 ]. It is also known that the “thin-ply effect” can be obtained, which improves the mechanical properties of the composite materials by reducing the thickness of the prepreg to an extremely low level [ 27 , 28 ]. It is expected that a further fiber-spreading treatment of commingled yarns, consisting of thermoplastic and carbon fibers, could produce superior CFRTP, but few studies have been conducted toward that end.…”
Section: Introductionmentioning
confidence: 99%
“…The steel blunt nose impactor (see Figure 1c) with 17 kg of weight and 40mm diameter (d) was used through drop weight impact method [14][15][16]. This method was applied where, the impactor dropped at various altitudes of 1.2 m, 1.4 m and 1.6 m which equal to 4.8 m/s, 5.2 m/s and 5.6 m/s respectively.…”
Section: Methodsmentioning
confidence: 99%